2014
DOI: 10.33549/physiolres.932878
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Oophorectomy May Have an Unfavorable Effect on Glucose Metabolism Compared With Natural Menopause

Abstract: The incidence of diabetes mellitus is rising worldwide. The aim of this prospective epidemiological study was to compare the effects of natural and surgical menopause on parameters of glucose metabolism. In a group of 587 repeatedly examined women, with a baseline age of 45-55 years, the following subgroups of women were separated: those after bilateral oophorectomy (BO, n=37) and those in natural menopause (NAT, n=380) including women menopausal already at baseline (POST, n=89). The study parameters including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…bilateral oophorectomy overall or a reduced risk associated with bilateral oophorectomy in a subgroup compared with premenopausal women. Two studies (21,22) observed an increased risk of diabetes in women who underwent hysterectomy concomitant with BSO, which is in line with our finding. However, Lejsková et al (22) did not examine the association between hysterectomy alone and risk of diabetes, and Appiah et al (21) observed a nonsignificantly increased risk of diabetes associated with hysterectomy alone (HR = 1.38, 95% CI: 0.94, 2.04).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…bilateral oophorectomy overall or a reduced risk associated with bilateral oophorectomy in a subgroup compared with premenopausal women. Two studies (21,22) observed an increased risk of diabetes in women who underwent hysterectomy concomitant with BSO, which is in line with our finding. However, Lejsková et al (22) did not examine the association between hysterectomy alone and risk of diabetes, and Appiah et al (21) observed a nonsignificantly increased risk of diabetes associated with hysterectomy alone (HR = 1.38, 95% CI: 0.94, 2.04).…”
Section: Discussionsupporting
confidence: 92%
“…Two studies (21,22) observed an increased risk of diabetes in women who underwent hysterectomy concomitant with BSO, which is in line with our finding. However, Lejsková et al (22) did not examine the association between hysterectomy alone and risk of diabetes, and Appiah et al (21) observed a nonsignificantly increased risk of diabetes associated with hysterectomy alone (HR = 1.38, 95% CI: 0.94, 2.04). In fact, the magnitude of the association found by Appiah et al is greater than our adjusted point estimate of 1.15 (95% CI: 1.07, 1.24) for hysterectomy only.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike natural menopause when falls in E2 occur within a few years, in surgical menopause created by bilateral oophorectomy, E2 ovarian production is cut rapidly and the reproductive life is suddenly terminated. Two previous studies have shown that there is a greater risk of DM in women with surgical menopause (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies unanimously indicated a significantly higher risk of developing diabetes in surgically induced menopausal women. [10][11][12][13] The potential mechanisms linking menopause and diabetes include increased adiposity and changes in sex hormones. [14][15][16][17] The most commonly investigated underlying pathophysiologies of T2D are insulin resistance (IR) and impaired insulin secretion.…”
Section: Introductionmentioning
confidence: 99%